Analysis Of 5R Implementation at Nala Husada Dental Hospital Surabaya - Caecilia Indarti; Endah Wahjuningsih; Arya Brahmanta (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction. The 5S culture (Sort, Set Order, Shine, Standardize, Sustain) is a culture adopted from Japan, a way of building and maintaining a clean, comfortable and set order environment. The implementation of the 5S culture at the Nala Husada Dental Hospital will have an impact on the process of improving safety and service quality which is an important component of service to patients. Initial survey results show that the 5S culture is not yet running, so it is a problem that needs to be solved. Materials and Methods. This type of research is experimental research. The 5S socialization was carried out to those in charge of units, as respondents totaling 39 people. This research began with a pre-test, socialization and post-test were carried out to measure understanding of the 5S. The 5S audit assessment was carried out on 28 service units and 38 non-service units. The 5S audit assessment uses the 5S LAM KPRS indicators. The 5S assessment audit was carried out twice. The results of the first audit are conveyed to all work units as an evaluation for improvement. After that, a second audit was carried out to see the follow-up to the results of the first audit. Results and Discussion. The results obtained were better understanding of knowledge and audit results after the 5S socialization. Pre-test score 59.17, post-test 80.51. The results of the first stage of the 5S audit total score for service units was 53.0%, non-service units 40.6%. The results of the second stage of the 5S audit showed an increase in the audit score. The total score of service units was 68% and non-service units 61.9% Conclusion. Understanding knowledge and 5S audit results shows an increase in 5S awareness. 5S audits must continue to be carried out consistently and continuously, and require commitment.